2006
DOI: 10.1248/bpb.29.1952
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the Liver to Perfluorinated Fatty Acids with Different Carbon Chain Length in Male and Female Mice:In Relation to Induction of Hepatomegaly, Peroxisomal .BETA.-Oxidation and Microsomal 1-Acylglycerophosphocholine Acyltransferase

Abstract: Perfluorinated fatty acids (PFCAs), straight chain fatty acid analogues of which all aliphatic hydrogens are substituted with fluorine are primarily used as industrial materials, because of their surfactant properties, and their chemical and thermal stability. 1) Of PFCAs, perfluorooctanoic acid (PFOA) was the most widely used as a reactive intermediate in the industrial synthesis of fluoroacrylic esters, and its salts are used as processing aids in the production of fluoropolymer and fluoroelastmers and in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 25 publications
2
72
0
1
Order By: Relevance
“…Such hepatic effects of PFAAs are considered to be exerted via the peroxisome proliferator-activated receptor alpha (PPARα), but other mechanisms have also been suggested . Kudo et al (2006) reported that intraperitoneal administration of PFAAs with six-to nine-carbon length increased the liver weight and hepatic peroxisomal β-oxidation activity in mice, and the potency was in the order of perfluorononanonic acid (PFNA; C9) PFOA (C8) > perfluoroheptanoic acid (PFHpA; C7) > perfluorohexanoic acid (PFHxA; C6). In the other study, PFOA (C8) and perfluorodecanoic acid (PFDeA; C10) considerably increased the liver weight, and hepatic peroxisomal palmitoyl-and lauroyl-CoA oxidase activities, but the responses to perfluorobutanoic acid (PFBA; C4) were lower and perfluoroacetic acid (C2) was inactive in male mice fed a diet containing PFAAs (Permadi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such hepatic effects of PFAAs are considered to be exerted via the peroxisome proliferator-activated receptor alpha (PPARα), but other mechanisms have also been suggested . Kudo et al (2006) reported that intraperitoneal administration of PFAAs with six-to nine-carbon length increased the liver weight and hepatic peroxisomal β-oxidation activity in mice, and the potency was in the order of perfluorononanonic acid (PFNA; C9) PFOA (C8) > perfluoroheptanoic acid (PFHpA; C7) > perfluorohexanoic acid (PFHxA; C6). In the other study, PFOA (C8) and perfluorodecanoic acid (PFDeA; C10) considerably increased the liver weight, and hepatic peroxisomal palmitoyl-and lauroyl-CoA oxidase activities, but the responses to perfluorobutanoic acid (PFBA; C4) were lower and perfluoroacetic acid (C2) was inactive in male mice fed a diet containing PFAAs (Permadi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Data on the toxic properties of other PFAAs are limited, but they have been studied in recent years (Chengelis et al, 2009;Das et al, 2008;Fang et al, 2008;Lieder et al, 2009aLieder et al, , 2009bMertens et al, 2010;Shi et al, 2007;Stump et al, 2008;van Otterdijk 2007avan Otterdijk , 2007bZhang et al, 2008). Available data indicate that PFAAs with a longer carbon chain are eliminated more slowly from the body Ohmori et al, 2003), and their toxic potency increases by lengthening the carbon chain (Kudo et al, 2000(Kudo et al, , 2006Permadi et al, 1992). Since the bioaccumulation potential of PFAAs also increases depending on their carbon number (Martin et al, 2003), long-chain PFAAs may cause serious environmental and/or human health concerns in the future.…”
Section: Introductionmentioning
confidence: 99%
“…24) Our previous studies showed that, although a striking difference exists in the effects of PFCAs on the liver when they are estimated by the induction of AOX as a parameter, the induction of AOX by PFCAs depends on only the number of PFCA molecules, but not the difference in their perfluoroalkyl chain length with regard to the difference in the extent of the induction. [22][23][24] These findings suggest that PFCAs with a perfluoroalkyl chain of 6-10 carbons have almost the same potency as a ligand for peroxisome proliferator-activated receptor (PPAR)a in the liver of rats, 22,24) since AOX is considered to be induced by peroxisome proliferators through the activation of PPARa.25) Our previous study demonstrated that the treatment of male rats with PFOA evidently changed the acyl composition of hepatic phospholipids and that the changes were, in part, elucidated by the induction of stearoyl-CoA desaturase (SCD) by PFOA.26) To date, however, little informa- …”
mentioning
confidence: 99%
“…19,20) PFOA was shown to be accumulated in the liver of rats and mice and to cause hepatomegaly, 21) induction of enzymes including peroxisomal acyl-CoA oxidase (AOX) in particular [22][23][24] and accumulation of TG. 24) Our previous studies showed that, although a striking difference exists in the effects of PFCAs on the liver when they are estimated by the induction of AOX as a parameter, the induction of AOX by PFCAs depends on only the number of PFCA molecules, but not the difference in their perfluoroalkyl chain length with regard to the difference in the extent of the induction.…”
mentioning
confidence: 99%
“…Supporting this finding, recent studies observed that the potency of PFHxA at the human peroxisome-proliferator activated receptor (PPAR)α, activation of which is associated with decreased blood lipid levels, is approximately half the potency of PFOA in the human hepatocellular carcinoma cell line HepG2 [42•] and approximately six-fold less potent than PFOA in both mouse and human PPARα in transiently transfected COS cells [43•]. Additionally, the decreased retention of PFHxA in the liver compared with the longer-chained compounds such as PFOA greatly decreases its potency to induce hepatic peroxisomal proliferation in vivo [44]. Concomitant with these findings, there was also no association of PFHxA serum levels (0.03 ng/ml median) with blood lipids in a Chinese population [45•].…”
Section: Systemic and Reproductive Toxicologymentioning
confidence: 99%